Bahasa Inggris - Nabil, Mohammad Adib (Jurusan Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jenderal Soedirman, 2025)
This study explores the transformation of question-and-answer dynamics as a catalyst for developing communicative competencies among Office Administration Education students. The